A Socialization of Village Map Preparation in Sempajaya Village, Karo Regency - Harefa, Mei Brilian; Dasrizal, Dasrizal; Hendri, Sufrial; Rizalitaher, Alif Saum; Tarigan, Hosea; Timoti, Sandros (PT FORMOSA CENDEKIA GLOBAL, 2024)
A village is a government unit that is given customary autonomy rights so that it is a legal entity. Village maps are basic thematic maps that contain natural elements and special theme elements that can be presented in image maps, facilities and infrastructure maps, as well as land cover and land use maps. Sempajaya Village is a village located in Berastagi District, Karo Regency, North Sumatra Province. A village map is one of the important things a village has in order to develop a roadmap for development and regional planning as well as maximizing the village's potential. Tourism and agrotourism villages are the potential of Sempajaya Village. So it is deemed necessary to have a village map which includes regional boundaries, land use, tourism potential, road access and other facilities.